(3eYLe eG ESJYLes - (3CHhYHjO GdHcQjs
(3ChdgG (B:s
( (3CbjS ajge HGdMQI MQI Hfi Sdje hMQI Hfi gdGd (B) (3bHd HGH MQa GdgeRI hGdCda s
(3BNQgG (B:s
(3jfJgi HJQLeI RHjO ef cJGH MQa GdRGi (B( (3HdO HGdjef eYQha hRHjO (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3eQJH Ydi MQha GdgLGAs
(3Ydi GdJQJjH GdeZQHis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1737s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs